ARE Z GENERATION YOUNG PEOPLE POTENTIAL INVESTORS IN SUSTAINABLE FINANCE? - RIBAU-PELTRE, Nadege (Bankers, Markets & Investors, 2023)
Given the amounts at stake to make the planet more sustainable in the coming years, at least at the European level, public investment will certainly not be sufficient to channel the necessary sums. It therefore seems essential to direct private financial flows into activities that are compatible with the general direction taken. We wanted to question the capacity of young French people of Z Generation, who are the investors of tomorrow, to take on the role of future sustainable investors. We highlighted three groups of individuals with different knowledge and attitudes towards traditional and sustainable investment. Oneof these groups, representing more than half of the respondents, includes individuals with the most favorable attitude towards sustainable investment, but with little knowledge of investment and a rather negative attitude towards traditional investment. These results lead us to wonder about the origins of this attitude towards sustainable investment.